2015
DOI: 10.1038/npjpcrm.2014.102
|View full text |Cite
|
Sign up to set email alerts
|

Methodological quality of meta-analyses on treatments for chronic obstructive pulmonary disease: a cross-sectional study using the AMSTAR (Assessing the Methodological Quality of Systematic Reviews) tool

Abstract: Background:Meta-analysis (MA) of randomised trials is considered to be one of the best approaches for summarising high-quality evidence on the efficacy and safety of treatments. However, methodological flaws in MAs can reduce the validity of conclusions, subsequently impairing the quality of decision making.Aims:To assess the methodological quality of MAs on COPD treatments.Methods:A cross-sectional study on MAs of COPD trials. MAs published during 2000–2013 were sampled from the Cochrane Database of Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 28 publications
(30 reference statements)
4
33
0
Order By: Relevance
“…That study only found that 60% of the 125 included SRs only met four of the 11 AMSTAR methodological criteria. When compared with MAs in other clinical areas, MAs in DM performed no better than those focused on pharmacist health intervention (11), Chinese herbal medicine interventions (12) as well as treatment for chronic obstructive pulmonary disease (13). Our regression analyses showed that MAs published more recently were significantly related to better performance.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…That study only found that 60% of the 125 included SRs only met four of the 11 AMSTAR methodological criteria. When compared with MAs in other clinical areas, MAs in DM performed no better than those focused on pharmacist health intervention (11), Chinese herbal medicine interventions (12) as well as treatment for chronic obstructive pulmonary disease (13). Our regression analyses showed that MAs published more recently were significantly related to better performance.…”
Section: Discussionmentioning
confidence: 55%
“…These MAs usually draw more favorable conclusions for the financially supported intervention (17,18). Unfortunately, it is difficult for readers to detect such sponsorship as majority of authors did not state sources of support for both the MA and for each of the included primary studies (10,12,13,19). Only 7.5% of included MAs reported this information comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…AMSTAR (Assessing the Methodological Quality of SR) also came out to be a validated tool as a guide to develop and evaluate reviews and it featured with good agreement and construct validity . Under the guidance of PRISMA statement or AMSTAR tool, assessments of the reported methodology of MAs in various fields were published previously, including fields of surgery, pulmonary disease, telerehabilitation and nursing …”
Section: Introductionmentioning
confidence: 99%
“…Methodological quality of MAs on the treatments of primary hypertension showed better performance in the majority of the AMSTAR items than that of MAs in orthodontics and nursing, except for providing protocol and stating sources of supports. On the other hand, our included MAs had worse performance in the majority of AMSTAR items than MAs on Chinese herbal medicine and chronic obstructive pulmonary disease …”
Section: Discussionmentioning
confidence: 95%
“…However, methodological shortcomings of MAs may influence the trustworthiness of synthesis findings and may subsequently mislead decision‐making . Previous appraisals of MAs in other healthcare disciplines have shown varying extents of methodological limitations . The rigor of MAs on hypertension treatments has not yet been assessed in a comprehensive manner.…”
mentioning
confidence: 99%